International Rugby Board Rugby World Cup 2007 injury surveillance study. Issue 6 (6th June 2008) - Fuller, C W; Laborde, F; Leather, R J; Molloy, M G
Abstract : Objective: to determine the incidence, nature and causes of injuries sustained during the International Rugby Board (IRB) Rugby World Cup 2007. Design: Pospective, whole-population survey. Population: 626 international rugby players representing 20 teams competing at the IRB Rugby World Cup 2007 in France. Methods: The survey followed the international consensus procedures for studies of injuries in rugby union; the main outcome measures were incidence of match and training injuries (number of injuries/1000 player hours), severity (days absence), location, type and cause of injury. Results: the incidence of injuries was 83.9/1000 player-match hours (forwards 84.0; backs 83.7) and 3.5/1000 player-training hours (forwards 3.5; backs 3.6). The average severity of injuries was 14.7 days (forwards 14.0; backs 15.5) during matches and 17.8 (forwards 15.9; backs 19.8) during training. Lower limb muscle and ligament injuries were the main injuries during both matches and training. Most injuries were sustained in the tackle during matches and in full-contact skills activities during training. Conclusions: This study shows the application of the methodology described in the international consensus statement on injury surveillance studies in rugby union and provides benchmark values for the incidence, severity, nature and causes of match and training injuries sustained during the IRB Rugby World Cup.